UPAYA MENINGKATKAN KETERAMPILAN MEMBACA MELALUI MEDIA CERITA BERGAMBAR PADA SISWA KELAS 2 SD INPRES PERUMNAS - Hesti Londong Padang; Nurvita; Samsu Alam (LPPM Universitas Cipta Mandiri, 2025)
Based on observations at SD Inpres Perumnas, students' reading skills are low. This is reflected in the low ability of students to understand the meaning of the text in depth, the lack of ability to identify important information in reading, as well as difficulties in analyzing and drawing conclusions from the text. This research is a Classroom Action Research (CAR) which involves four stages: planning, action implementation, observation, and reflection. Classroom action research is a strategy that can be utilized by teachers to identify various problems related to learning in the classroom. The researcher acts as a planner of learning activities, while the teacher functions as the implementer of these activities. The researcher, with the help of peers, observed learning activities related to reading interest. The results of the research and discussion show that the use of picture story media has the potential to improve the reading ability of grade 2 students of SD Inpres Perumnas in Indonesian language learning. The improvement of reading skill test results in cycle I and cycle II showed significant progress.